EFEK KOMBINASI PAKAN ALAMI (Artemia sp. dan Oithona sp.) TERHADAP TINGKAT KELULUSHIDUPAN LARVA UDANG VANAME (Litopenaeus vannamei) - Chilmawati, Diana; Suminto, Suminto (Jurnal Akuakultur Rawa Indonesia, 2020)
The development of vaname shrimp (Litopenaeus vannamei) culture will affect the increasing need of live food organisms for shrimp larvae, especially Artemia sp. In shrimp hatchery, biotechnical constraints of culture of Artemia sp. and dependence on imported cysts is a limiting factor for success. Perhaps, the use of Oithona sp. is an alternative live food for L. vannamei larvae which has the potential to be combined with Artemia sp. The aim of this study was to examine the effect of a combination of live foods, Artemia sp. and Oithona sp. on the survival rate of L. vannamei shrimp larvae and to determine the percentage of live food combinations that provide the best survival rate of L. vannamei shrimp larvae. The method used was an experiment carried out at the Coastal Area Development Laboratory, Jepara. The experimental design used CRD with 5 treatments and 4 replications. Those treatments were a combination of live food, Artemia sp. and Oithona sp. with the percentage ratio of each treatment A. 100%: 0%; B. 75%: 25%; C. 50%: 50%; D. 25%: 75%; and E. 0%: 100%. The results showed that the combination of live foods of Artemia sp. and Oithona sp. had a significant effect (p<.05) on the survival rate of the L. vannamei  shrimp larvae and the percentage of the combination of natural foods, Artemia sp. ranged of 50 -100% and Oithona sp ranged of 0% - 50% had given the survival rates of L. vannamei larvae (N-5/6 to PL-10)  ranged of 41.71-43.00%.